PERAN LINGKUNGAN KELUARGA TERHADAP KEMAMPUAN LITERASI PADA SISWA SEKOLAH DASAR - Lalu Muhammad Rizki Farobi Khair; Rizki Dewina Shanty; Qorik Atun Hafizah; Nur Dwi Safitri; Nuraeni; Hadiyatul Rodiyah; Imron Husen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
literacy skills are a fundamental basis for elementary school students to develop thinking skills, comprehend information, and communicate effectively. The family environment plays a significant role in shaping a child's literacy skills from an early age. This article aims to examine how the family environment contributes to the development of literacy in elementary school students. The method used is a literature review, analyzing various studies and theoretical sources related to the role of the family in children's literacy education. The results of the study indicate that active parental involvement, the availability of reading materials at home, the habit of reading together, and positive communication between parents and children are key factors in enhancing literacy skills. Thus, collaboration between family and school needs to be improved to realize a sustainable literacy ecosystem.